Clinical characteristics and myocardial function assessed by traditional and novel echocardiographic methods in competitive triathletes with and without myocardial fibrosis. (25th November 2020) - Knappe, D; Muench, J; Yildirim, S; Witzel, K; Tahir, E; Lund, G; Blankenberg, S; Patten, M
Abstract: Background: The aim of the present study was to compare clinical characteristics and cardiac structure and function in competitive triathletes with and without myocardial fibrosis. Methods: Cardiac fibrosis in 61 healthy male competitive triathletes (>10 hrs of training per week, age 45±10 yrs) was quantified using LGE-sequences in CMR (1.5 tesla scanner). Transthoracic echocardiography, physical examination, past medical history and routine lab diagnosis for exclusion of other conditions were performed. Baseline characteristics like blood pressure at rest (BP), bodymass-index (BMI), and systolic and diastolic echocardiographic parameters (left atrial volume index (LAVI), e', E, A, right ventricular pressure gradient) as well as global longitudinal strain, were analysed by two independent observers blinded to the CMR measurements. Triathletes were sub-divided into LGE-positives (LGE+) vs. LGE-negatives (LGE-). Results: All individuals appeared healthy with no drug history. Focal non-ischaemic LGE was detected in 19 triathletes. Compared to LGE-negative triathletes, LGE-positives showed significantly higher systolic BP (142 vs. 128 mmHg, p=0.004). Logistic regression showed, that per 10 mmHg enhanced blood pressure the chance for LGE rises by 89%. Triathletes with and without LGE demonstrated no difference in conventional echocardiographic measurements such as left ventricular ejection fraction and volumes and no difference in diastolic parameters. But the presence of MF did mediate global longitudinal strain (GLS). Global longitudinal strain was significantly reduced in LGE positive athletes (LGE+: −19.8±3.4; LGE-: −21.7±2.4, p=0.04) Conclusions: Reduced global longitudinal strain mediated as an early echocardiographic marker for subclinical changes in asymptomatic competitive triathletes with myocardial fibrosis compared to triathletes without LGE. Novel echocardiographic parameter such as longitudinal strain might serve as an easy tool to identify high endurance athletes at higher risk for cardiovascular events and that individuals with enhanced blood pressure should undergo cardiac consultation before starting endurance-training in competitive disciplines. Funding Acknowledgement: Type of funding source: None